Reverse time migration and full waveform inversion in riemannian manifolds : application to rugged topography (2018)
ABSTRACT: RTM is an imaging technique that although was introduced in the year 1983 (E. Baysal and Sherwood, 1983) has only been extensively used in the last few years because the computational resources needed to implement it were only available recently. Despite its high computational cost, RTM is nowaday’s choice among a wide set of options to produce seismic images because it can be used in zones with strong variations of the velocity of propagation, it can map sub-surface structures with any dipping angle and can create good images of zones of interest like those under and around salt domes where hydrocarbon reservoirs can be found. The classical RTM algorithm produces images of the earth’s sub-surface by means of controlled seismic waves. These waves are generated mechanically using seismic sources such as vibroseis (a truck-mounted vibrator) or controlled explosions among others. Figure 1 (SaharaWealth Advisors, 2015) shows a typical field setup used to get the seismic data, required as the starting point for the RTM method.